Politicization of psychiatry and the improvement of ethical standards in the 1970s - Kosenko, Oxana; Steger, Florian (Frontiers in Psychiatry, 2023)
Background: The Code of Ethics for Psychiatry adopted by the World Psychiatric Association in 1977, also known as the Declaration of Hawaii, was a milestone in the development of ethical standards in psychiatry. The impetus for the development of the code came primarily from the politicization of psychiatry, first discovered in the USSR, and later in other countries of the socialist camp, such as Romania, Yugoslavia, and the People’s Republic of China. The purpose of this article is to trace reasons for the lack of consolidation among Western psychiatrists against the politicization of psychiatry and their efforts to improve the ethical standards for this medical field. Methods: We analyzed unpublished documents from the Archive of the German Association for Psychiatry, Psychotherapy and Psychosomatics, the private archives of the West German psychiatrists Gerd Huber and Walter von Baeyer as well as research works. To examine these sources, we implemented the historical-critical method. Results: The World Psychiatric Association made efforts to collect, analyze and discuss materials concerning psychiatric ethics to create the Code of Ethics for Psychiatry and establish an Ethical Committee. In general, the reaction of Western psychiatrists to information about the internment of dissidents in psychiatric hospitals was restrained and focused on attempts to solve the issue together with the Soviet colleagues. Conclusion: The international policy of détente of the time as well as collisions between different medical concepts and ethical dimensions did not allow Western psychiatrists to condemn cases of politicization of psychiatry without clarification of the situation. The World Psychiatric Association’s efforts in the ethical field improved the ethical standards for psychiatry.